Ameliorative effects of plant growth promoting bacteria, zinc oxide nanoparticles and oxalic acid on Luffa acutangula grown on arsenic enriched soil. (1st May 2022) - Tanveer, Yashfa; Yasmin, Humaira; Nosheen, Asia; Ali, Sajad; Ahmad, Ajaz
Abstract: Arsenic (As) contamination and bioaccumulation are a serious threat to agricultural plants. To address this issue, we checked the efficacy of As tolerant plant growth promoting bacteria (PGPB), zinc oxide nanoparticles (ZnO NPs) and oxalic acid (OA) in Luffa acutangula grown on As rich soil. The selected most As tolerant PGPB i.e Providencia vermicola exhibited plant growth promoting features i.e solubilzation of phosphate, potassium and siderophores production. Innovatively, we observed the synergistic effects of P. vermicola, ZnO NPs (10 ppm) and OA (100 ppm) in L. acutangula grown on As enriched soil (150 ppm). Our treatments both as alone and in combination alleviated As toxicity exhibited by better plant growth and metabolism. Results revealed significantly enhanced photosynthetic pigments, proline, relative water content, total sugars, proteins and indole acetic acid along with As amelioration in L. acutangula. Furthermore, upregulated plant resistance was manifested with marked reduction in the lipid peroxidation and electrolyte leakage and pronounced antagonism of As and zinc content in leaves under toxic conditions. These treatments also improved level of nutrients, abscisic acid and antioxidants to mitigate As toxicity. This marked improvement in plants' defense mechanism of treated plants under As stress is confirmed by less damaged leaves cell structures observed through the scanning electron micrographs. We also found substantial decrease in the As bioaccumulation in the L. acutangula shoots and roots by 40 and 58% respectively under the co-application of P. vermicola, ZnO NPs and OA in comparison with control. Moreover, the better activity of soil phosphatase and invertase was assessed under the effect of our application. These results cast a new light on the application of P. vermicola, ZnO NPs and OA in both separate and combined form as a feasible and ecofriendly tool to alleviate As stress in L. acutangula. Highlights: Among 14 rhizobacteria strains P. vermicola displayed the highest As tolerance. As resistance is induced by ZnO NPs (10 ppm) in L. acutangula. The oxalic acid (OA) at 100 ppm chelate arsenic effectively. The synergistic effect of combined treatment for As resistance was observed. This combination modulates soil and plant enzymatic activities to induce arsenic resistance.